Phase analysis study of the copper-aluminum contact pair obtained by plasma dynamic method; IOP Conference Series: Materials Science and Engineering; Vol. 66: 20th International Conference for Students and Young Scientists: Modern Techniques and Technologies (MTT'2014), Tomsk, Russia, 14-18 April 2014 - Sivkov A. A. Aleksander Anatolyevich; Saygash A.; Kolganova J. L. Julia Leonidovna; Shanenkov I. I. Ivan Igorevich (2014, 2014)
Title screen